Neocosmospora rubicola, a stem rot disease in potato: Characterization, distribution and management - Riaz, Muhammad; Akhtar, Naureen; Msimbira, Levini A.; Antar, Mohammed; Ashraf, Shoaib; Khan, Salik Nawaz; Smith, Donald L. (Frontiers in Microbiology, 2022)
Potato (Solanum tuberosum L.) is one of the most important crops in maintaining global food security. Plant stand and yield are affected by production technology, climate, soil type, and biotic factors such as insects and diseases. Numerous fungal diseases including Neocosmospora rubicola, causing stem rot, are known to have negative effects on potato growth and yield quality. The pathogen is known to stunt growth and cause leaf yellowing with grayish-black stems. The infectivity of N. rubicola across a number of crops indicates the need to search for appropriate management approaches. Synthetic pesticides application is a major method to mitigate almost all potato diseases at this time. However, these pesticides significantly contribute to environmental damage and continuous use leads to pesticide resistance by pathogens. Consumers interest in organic products have influenced agronomists to shift toward the use of biologicals in controlling most pathogens, including N. rubicola. This review is an initial effort to carefully examine current and alternative approaches to control N. rubicola that are both environmentally safe and ecologically sound. Therefore, this review aims to draw attention to the N. rubicola distribution and symptomatology, and sustainable management strategies for potato stem rot disease. Applications of plant growth promoting bacteria (PGPB) as bioformulations with synthetic fertilizers have the potential to increase the tuber yield in both healthy and N. rubicola infested soils. Phosphorus and nitrogen applications along with the PGPB can improve plants uptake efficiency and reduce infestation of pathogen leading to increased yield. Therefore, to control N. rubicola infestation, with maximum tuber yield benefits, a pre-application of the biofertilizer is shown as a better option, based on the most recent studies. With the current limited information on the disease, precise screening of the available resistant potato cultivars, developing molecular markers for resistance genes against N. rubicola will assist to reduce spread and virulence of the pathogen.